2011
DOI: 10.1128/jvi.00859-11
|View full text |Cite
|
Sign up to set email alerts
|

Avian-Type Receptor-Binding Ability Can Increase Influenza Virus Pathogenicity in Macaques

Abstract: The first influenza pandemic of the 21st century was caused by novel H1N1 viruses that emerged in early 2009. An Asp-to-Gly change at position 222 of the receptor-binding protein hemagglutinin (HA) correlates with more-severe infections in humans. The amino acid at position 222 of HA contributes to receptor-binding specificity with Asp (typically found in human influenza viruses) and Gly (typically found in avian and classic H1N1 swine influenza viruses), conferring binding to human-and avian-type receptors, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 33 publications
4
40
1
Order By: Relevance
“…6). In agreement with previous studies (5,19,35,38), these results suggest that an Asp-to-Gly amino acid change at position 222 of the HA of Norway3487 virus confers the ability to recognize both avian-type and human-type receptors.…”
Section: Fig 3 Virus Titers In Respiratory Washes From Infected Cynomsupporting
confidence: 81%
See 3 more Smart Citations
“…6). In agreement with previous studies (5,19,35,38), these results suggest that an Asp-to-Gly amino acid change at position 222 of the HA of Norway3487 virus confers the ability to recognize both avian-type and human-type receptors.…”
Section: Fig 3 Virus Titers In Respiratory Washes From Infected Cynomsupporting
confidence: 81%
“…The more pathogenic Norway3487 virus has the Asp-to-Gly change at position 222 of its HA, conferring avian-type receptor-binding specificity. Thus, this change may result in more efficient infection of human alveolar type II pneumocytes, which express avian-type receptors, reducing the availability of progenitor cells for essential lung functions and thus leading to severe pulmonary impairment, diffuse alveolar damage, and respiratory distress, culminating in the increased pathogenicity in nonhuman primates described previously (35,37). Moreover, we found that PB2 derived from Norway3487 virus contributed to higher polymerase activity, possibly leading to more efficient viral replication in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, severe viral pneumonia attributed to efficient virus attachment to α2,3-sialic acid glycoconjugates deep in the lungs have been observed in H5N1 (25) and HA 225G variants of the pH1N1 (5,(26)(27)(28)(29)(30) virus infections. Moreover, it has been demonstrated that avian-type receptor-binding ability because of HA 225G increased pathogenicity of the pH1N1 2009 virus in nonhuman primates (31).…”
Section: Discussionmentioning
confidence: 99%